Methylation of the Vitamin D Receptor (VDR) Gene, Together with Genetic Variation, Race, and Environment Influence the Signaling Efficacy of the Toll-Like Receptor 2/1-VDR Pathway - Meyer, Vanessa; Saccone, Donovan Sean; Tugizimana, Fidele; Asani, Furaha Florence; Jeffery, Tamsyn Jacki; Bornman, Liza (Frontiers in Immunology, 2017)
Background. The disparity in prevalence of infectious diseases across the globe is common knowledge. VDR-mediated TLR2/1 signaling produce antimicrobial peptides which is critical as a first line of defense in innate immunity. Numerous studies disclosed the independent role of genetic polymorphisms in this pathway, vitamin D status or season and more recently epigenetics, as factors contributing to infectious disease predisposition. Few studies address the interaction between environment, genetics and epigenetics. Here we hypothesized that VDR-mediated TLR2/1 signaling is influenced by a combination of environment, epigenetics and genetics, collectively influencing differential innate immunity. Methods. Healthy Black and White South Africans (n = 100) donated blood, while UVI was recorded for the duration of the study. LC-MS/MS supported 25(OH)D3 quantification. Monocyte/macrophage cultures, supplemented with/without 1,25(OH)2D3, were activated with the TLR2/1 elicitor, Pam3CSK4. VDR, CAMP, hCAP-18 and CYP24A1 expression were quantified by RT-qPCR or flow cytometry. Pyrosequencing facilitated VDR methylation analysis and SNP genotyping in regions pinpointed through a bioinformatics workflow. Results. Season interacted with race showing 25(OH)D3 deficiency in Blacks. UVI correlated with 25(OH)D3 and VDR methylation, likely influencing race differences in the latter. Regarding the TLR2/1 pathway, race differences in SNP genotype distribution was confirmed and functional analysis of VDR-mediated signaling showed interaction between race, season and 25(OH)D3 status. Multivariate OPLS-DA analysis mirrored several interactions between UVI, 25(OH)D3 status, DNA sequence and methylation variants. Methylation of the promoter CGI 1062 CpG 3 significantly discriminates a 5.7 fold difference between mean VDR protein levels upon TLR2/1 elicitation, the variation of which is further influenced by 25(OH)D3 status and the VDR SNP TaqI. Conclusions. Regulation of VDR-mediated TLR2/1 signaling is multifactorial, involving interaction between environment (UVI and consequent 25(OH)D3 status), epigenetics (VDR methylation at key regulatory sites) and genetics (TLR1, TIRAP and VDR SNPs).